2008
DOI: 10.1016/j.psychres.2007.08.020
|View full text |Cite
|
Sign up to set email alerts
|

Attention deficit in depressed suicide attempters

Abstract: Attention is typically impaired in depression and may play a role in risk for suicidal behavior. In this study, 66 non-patients, 83 depressed subjects with no past history of suicide attempt, 53 depressed subjects with one or more low lethality suicide attempts, and 42 depressed subjects with at least one high lethality attempt were compared on two computerized measures of attention, a Continuous Performance Test (CPT) and a Stroop task. All subjects were medication free at the time of assessment. Attention wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
129
2
5

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 187 publications
(151 citation statements)
references
References 57 publications
15
129
2
5
Order By: Relevance
“…Lower performance in suppression and restraint function of cognitive inhibition. Analyzing the studies according to the type of affective disorders, executive dysfunction with cognitive inhibition were observed in patients with major depression with a history of severe suicide attempts, 39,40 depressed patients who attempted suicide, 32,42 and depressed patients with suicidal ideations. 47 For patients with BD, more executive dysfunction and cognitive inhibition deficit was found among BD-II, compared with BD-I, patients who attempted suicide, 35 and BD-I patients with suicide attempts, compared with patients with nonsuicide attempts BD-I.…”
Section: Altered Inattention Component Of Cognitive Inhibitionmentioning
confidence: 99%
“…Lower performance in suppression and restraint function of cognitive inhibition. Analyzing the studies according to the type of affective disorders, executive dysfunction with cognitive inhibition were observed in patients with major depression with a history of severe suicide attempts, 39,40 depressed patients who attempted suicide, 32,42 and depressed patients with suicidal ideations. 47 For patients with BD, more executive dysfunction and cognitive inhibition deficit was found among BD-II, compared with BD-I, patients who attempted suicide, 35 and BD-I patients with suicide attempts, compared with patients with nonsuicide attempts BD-I.…”
Section: Altered Inattention Component Of Cognitive Inhibitionmentioning
confidence: 99%
“…In the first comprehensive study of cognitive performance in attempted suicide, Keilp and colleagues (10) found evidence of executive deficits in high-lethality suicide attempters, specifically on tasks requiring organization and focused effort: the Stroop interference task, the A not B task, verbal fluency task, and the Wisconsin Card Sorting Task (WCST), where suicide attempters failed to maintain cognitive set (10). Subsequent studies have found impairment in specific aspects of executive function, including attentional control (11, 15), response inhibition (14), and verbal fluency (9). However, the findings of these studies are inconclusive; their implications for the cognitive diathesis of suicide are complicated by small sample sizes, the inclusion of individuals with a distant history of suicidal behavior and depression, and especially the lack of suicide ideator control groups.…”
Section: Introductionmentioning
confidence: 99%
“…The present case-control study aimed to examine whether executive function impairments are associated with contemplation of suicide (16), suicidal behavior (10, 11, 17), or both, in late life, above and beyond the effect of depression. Thus, we report performance on the EXIT in both suicide attempters and suicide ideators separately, compared with groups of non-suicidal depressed older adults, and older adults with no lifetime psychiatric history.…”
Section: Introductionmentioning
confidence: 99%
“…Plusieurs études ont mis en évidence de moins bonnes performances exécutives (inflexibilité mentale réactive et conceptuelle, diminution de la fluence verbale et des capacités de catégorisation) des suicidants en comparaison de témoins affectifs chez la personne d'âge moyen (Keilp et al, 2001 ;Keilp et al, 2008 ;Marzuk et al, 2005 ;Raust et al, 2007 ;Malloy-Diniz et al, 2009) et âgée (Dombrovski et al, 2008a ;King et al, 2000 ;McGirr et al, 2011). Les résultats sont contradictoires dans des populations de suicidants hétérogènes au plan diagnostic (Bartfai et al, 1990 ;Burton et al, 2011 ;Ellis et al, 1992).…”
Section: Neuropsychologie Des Conduites Suicidaires Les Fonctions Exéunclassified
“…Son déficit est associé chez la personne déprimée à une recrudescence de ruminations, facteur d'idées suicidaires (Morrison et O'Connor, 2008 ;Joormann et Gotlib, 2010). Un déficit de l'inhibition cognitive est suggéré chez des déprimés suicidants ou suicidaires plus jeunes (Keilp et al, 2008 ;Westheide et al, 2008 ;Harkavy-Friedman et al, 2006).…”
Section: L'inhibition Cognitiveunclassified